The Impact of Functional Training on Balance and Vestibular Function: A Narrative Review - Eric Bunnell; Matthew T. Stratton (Journal of Functional Morphology and Kinesiology)
Objectives: The objective of this narrative review was to examine the available literature regarding the increasingly popular method of exercise commonly referred to as “Functional Training” and its potential implications on vestibular and balance function. Methods: a narrative review of the experimental literature prior to September 2024 was conducted. To be included in this review, the selected investigations need to include some aspect of vestibular function, balance function, functional training, and/or functional movement and be conducted in humans. Results: Evidence emerged to support the claim that implementing a physical fitness training program may improve vestibular and balance function but that a functional training program or a physical fitness program designed to improve functional movements may improve vestibular and balance function to a greater extent. Additionally, these results may be altered by factors such as age and sex. Furthermore, while there is a multitude of literature regarding the impact of functional training on balance, few investigations combine these data with direct assessments of vestibular function. Conclusions: Functional training may aid in improving vestibular and balance function, along with scores on common tests such as the Y balance test. However, more research is necessary to elucidate the direct mechanisms by which functional training may impact vestibular and balance function.